Morphochemical characteristics and mixing state of long range transported wildfire particles at Ny-Ålesund (Svalbard Islands) - Moroni, Beatrice; Cappelletti, David; Crocchianti, Stefano; Becagli, Silvia; Caiazzo, Laura; Traversi, Rita; Udisti, Roberto; Mazzola, Mauro; Markowicz, Krystof; Ritter, Christoph; Zielinski, Tymon (2017)
A prolonged and exceptionally intense air mass advection event transporting biomass burning aerosols generated in Alaska affected Ny-Ålesund in the mid of July 2015. This paper reports the morphochemical characteristics and mixing state of individual aerosol particles collected during the event. To this aim aerosol samples were collected on nucleopore polycarbonate membrane filters using a DEKATI 12-stage low volume impactor and analyzed by scanning electron microscopy (SEM) techniques. Results of SEM investigations depict a complex aerosol characterized by an external mixing between a main part of carbonaceous organic particles (tar balls and organic particles), lower ammonium sulfate and minor potassium chloride and mineral dust amounts. The carbonaceous particles are spherical to slightly elongated and the organic particles show an internal mixing of low density organics and/or ammonium sulfate upon denser nuclei. Most particles are in the accumulation mode size range although the size and the morphology of the chloride and the sulfate salts evidence the growth of these species both in the air and upon the sampling membranes. Individual particle analyses were complemented by aerosol size distribution (Aerodynamic Particle Sizer, Scanning Mobility Particle Sizer) and optical (Particle Soot Absorption Photometer, nephelometer) measurements at ground level in order to retrieve the optical and radiative properties of the aerosol in the atmosphere and to predict the fate and behaviour of particles upon deposition at ground level. Individual particle analyses were also compared with bulk chemical analyses on daily sampling filters and back-trajectory analyses of the air mass movement in order to enucleate distinct sources of the aerosol during the long range transport.